Early displacement of an atrial lead: A fatal presentation of a relatively frequent complication - Caixal, Gala; Garcia-Hernando, Victor; Punti, Jordi; Ascoeta-Ortiz, Maria Soledad; Gusi, Gabriel; Martinez-Rubio, Antonio (JOURNAL OF CARDIAC ARRHYTHMIAS, 2025)
An 81-year-old woman was referred to Parc Taulí Hospital Universitari with complete atrioventricular block and a dual-chamber pacemaker was implanted. She subsequently presented an episode of ventricular tachycardia that degenerated into ventricular fibrillation requiring cardiopulmonary resuscitation. After review of the device, as well as the electrocardiogram and chest X-ray, displacement of the atrial lead into the right ventricle was confirmed. Contrary to expectations, the ventricular event was not secondary to endocardial irritation by the displaced lead, so the hypothesis of a possible depolarization-repolarization heterogeneity as a cause of the increased arrhythmogenicity was raised.